Modelling form deprivation myopia in experiment (Ukrainian Journal of Ophthalmology, 2026)
Background. Myopia, leading to visual function impairment, is one of the most topical issues in eye pathology. Although myopia is a common disease, its pathogenesis has a set of questions unstudied, which is why it is crucial to develop an axial myopia model on animals, a clinical picture of which is maximally similar to human and makes it possible to study both pathogenesis and treatment of myopia. So, the purpose of the present paper was to study certain parameters of the visual organ when modelling form deprivation myopia in rats under different light conditions. Material and Methods. Group 1 (10 animals) consisted of intact rats. Group 2 (15 animals) consisted of the rats, both eyelids of which were sutured to induce form deprivation myopia.  Group 3 (15 animals) were rats with eyelids sutured to induce form deprivation myopia which, unlike Group 2 rats, were kept under poor light conditions for 14 days. Within the same period, animals of Groups 1 and 2 were kept under natural light conditions. Once a 14-day period expired, sutures were taken out from the eyelids. After suture removal, all the animals were performed ultrasound scanning, tonometry (Maklakov applanation tonometer, a 2 g and 4 mm plunger) to measure intraocular pressure, and pachymetry (Handy Pachymetr SP–100) to measure corneal thickness. At two weeks after removal of sutures from the eyelids, the animals were sacrificed under general anesthesia and the eyeballs were enucleated. Objective criterion for myopia development was elongation of anterior-posterior dimension (APD) of the eyeball which was measured using ultrasound scanning (in vivo) and a digital sliding caliper (Topex) with 0.02 mm accuracy (post mortem). Data obtained were processed using the non-parametric Kruskall-Wallis and Mann-Whitney tests using a software program (Statistica 5.5).  Results. Our data on changes in visual organ parameters (intraocular pressure, corneal thickness, anterior-posterior dimension of the eyeball) in young rats when modelling form deprivation myopia under different light conditions showed more rapid progression of myopia when lighting was poor. Thus, the changes in the parameters involved in myopization were significantly more pronounced in the rats with an axial myopia model induced under poor light conditions as compared to those in experimental myopia under natural lighting (IOP was higher by 15.0%; APD was longer by 5.0%).Conclusions. Form deprivation myopia which is induced by eyelid suture in two-week-old rats in the period of eyeball growth under poor light conditions can be recommended for studying structural and functional characteristics of progressive myopia and developing pathogenetically-oriented treatment methods for the disease.
Keywords: form deprivation myopia; lighting; ultrasound scanning; tonometry; pachymetry; rats; experiment